1994
DOI: 10.1071/pp9940663
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Expansion Limits Dry Matter Accumulation of Salt-Stressed Maize

Abstract: Two maize (Zea mays L.) hybrids, differing in their salt tolerance (percentage of control on a dry weight basis) and ability to accumulate Na+ in the shoot, were treated with 80 mol m-3 NaCl salinity or 80 mol m-3 NaCl plus 8.75 mol m-3 CaCl2. Multiple harvests were performed and the interactions of salinity with time were examined with growth analysis. Relative growth rate (RGR) and leaf area ratio (LAR) were significantly reduced by NaCl salinity, but net assimilation rate (NAR) was unaffected. Supplemental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
29
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 0 publications
10
29
0
1
Order By: Relevance
“…These results showed that Tsushima was signifi cantly more tolerant to salinity than Pontivy. The dry-matter accumulation of salt-stressed maize was infl uenced by the degree of leaf expansion (Cramer et al, 1994). In the present experiments, PGR of both buckwheat species signifi cantly correlated with NAR (Tsushima; r = 0.983**, Pontivy; r=0.986**) and MLA (Tsushima; r = 0.982**, Pontivy; r=0.988**) as shown in Fig.…”
Section: Plant Growthsupporting
confidence: 50%
See 1 more Smart Citation
“…These results showed that Tsushima was signifi cantly more tolerant to salinity than Pontivy. The dry-matter accumulation of salt-stressed maize was infl uenced by the degree of leaf expansion (Cramer et al, 1994). In the present experiments, PGR of both buckwheat species signifi cantly correlated with NAR (Tsushima; r = 0.983**, Pontivy; r=0.986**) and MLA (Tsushima; r = 0.982**, Pontivy; r=0.988**) as shown in Fig.…”
Section: Plant Growthsupporting
confidence: 50%
“…These results showed that the interspecifi c difference in L 2 was mainly caused by the differences in GR L , LA L and SLA. In salt-stressed maize, leaf area ratio was signifi cantly lowered due to the reduction in SLA and leaf weight ratio, indicating that the salt stress altered leaf expansion and carbon allocation (Cramer et al, 1994). The increase in SLA might be important for the salt tolerance of maize because the degree of leaf expansion was related to SLA (Cramer et al, 1994).…”
Section: Leaf Expansionmentioning
confidence: 99%
“…Thus, the obtained results do not allow to distinguish definitively which variety is more tolerant to salinity. Various reports indicate that there are varietal differences in growth responses to salinity (Aslam et al 1993;Cramer et al 1994;Neumann 1997). However, Munns (2002 reported that during a short time in salinity it is difficult to assess the differences in plants salt tolerance, since the decrease in growth rate may be the same for species that have quite different reputations for salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In several other reports, it has been indicated that varietal differences in growth response to salinity could occur without sodium toxicity. For example, Cramer et al (1994) reported that in maize, leaf growth was more sensitive to salinity than the other plant parts and that the salt-sensitive cultivars accumulated less sodium than the salt-tolerant cultivars. A similar observation was noted for wheat, where the salt-tolerant lines showed much higher shoot Na+ levels than the sensitive lines (Schachmann and Munns 1992).…”
Section: Discussionmentioning
confidence: 99%